Feelings about Law/Justice. Rechtsgefühle The Relevance of Affect to the Development of Law in Pluralistic Legal Cultures. Die Relevanz des Affektiven für die Rechtsentwicklung in pluralen Rechtskulturen - Keiser, Thorsten; Olson, Greta; Reimer, Franz (Schriften des Rudolf-von-Jhering-Instituts Gießen, 2023)
Rechtsgefühle (feelings about law and justice) influence legal processes, politics as well as attitudes towards law, and have centrally impacted legal history. Using Rudolph von Jhering's The Struggle for Law (1872) as a point of departure, the essays explore 'legal feelings' as a sensus juridicus - a judge's effort to make legal norms fit the facts at hand -, as the emotions evoked by laws and legal processes, and as catalysts for legal reforms. Rechtsgefühle prove themselves pertinent with regard to the history of emotions, in respect to neuroscientific approaches to law and calls for computational law, and in terms of the ever thorny topic of how law should differ from politics. The authors argue for a plurality of Rechtsgefühle. With contributions by Prof. Dr. Gabriele Britz, Prof. Dr. Jeanne Gaakeer, Prof. Dr. Thorsten Keiser, Prof. Dr. Sylvia Kesper-Biermann, Prof. Dr. Frans-Willem Korsten, Prof. Dr. Greta Olson and Prof. Dr. Franz Reimer.